Investigation into the metabolomic effects of the non-canonical amino acid azetidine-2-carboxylic acid in neuroblastoma cells - Connor R. Phillips; Jake P. Violi; David S. Gertner; Joel R. Steele; David P. Bishop; Kenneth J. Rodgers (Food and Chemical Toxicology, 2026)

Individual Trees Respond to 40 Years of Climate Change Through Leaf Functional Trait Acclimation - Riley P. Fortier; Rodolfo Vásquez Martínez; Rocío Del Pilar Rojas Gonzalez; Rachel Collins; Luis Valenzuela Gamarra; Abel Montagudo Mendoza; Oliver L. Phillips; Timothy R. Baker; J. Sebastián Tello; Kenneth J. Feeley (Global Change Biology, 2026)
Forests are vital for regulating climate and sustaining biodiversity, but climate change threatens their ability to do so, especially in the tropics. Our knowledge of how tropical forests and their constituent trees will respond to changes in climate is largely based on functional trait studies; however, few previous studies have investigated trait changes within individual tropical trees across decades, limiting our ability to predict the future of these forests. In this study, we leveraged historical and contemporary botanical specimens collected from the same individual trees in the southern Peruvian Amazon, measured a suite of leaf traits to test for individual‐level trait changes over nearly 40 years, and then related these changes to concurrent changes in local climate. We hypothesized that trees have acclimated their functional traits in response to increasing air temperatures and drought intensification and that this acclimation should help to maintain stable leaf temperatures through time. In accord with our hypothesis, we found significant decreases in measured leaf traits, including size and shape metrics and stomatal traits, within individuals through time. We used these measured traits to model leaf temperatures through time, which increased faster than would be expected based on changes in air temperature alone. This accelerated warming of leaves was due to decreased stomatal conductance, a potential acclimation of trees to dry season intensification and rising [CO 2 ], thus limiting leaf transpirational cooling. In other words, trees have decreased abilities to cool their leaves, and consequently they may be approaching critical thermal thresholds faster than they would in the absence of water limitation. Our study provides evidence that while individual trees are acclimating to climate change, tropical forests are undergoing increasing thermal stress and that intensifying drought may be elevating this risk.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Iodophor Reduces Carnobacterium maltaromaticum and Vagococcus salmoninarum Prevalence During Brook Trout ( Salvelinus fontinalis ) Spawning - Justine Nelson; Rebekah McCann; Cristina Dahl; Keta Oettinger; Sara Dziki; Ryan Katona; Corey Puzach; Eric Leis; Brandon Keesler; Carey Edwards; Kenneth Phillips; Isaac Standish (Journal of Fish Diseases, 2026)
This study examines the effects of iodophor disinfection on the prevalence of Carnobacterium maltaromaticum and Vagococcus salmoninarum during several years of spawning brook trout ( Salvelinus fontinalis ) . The first year of the study, individual eggs were collected from females and separated into four treatment groups: unfertilised, unfertilised and disinfected, fertilised and fertilised and disinfected. Disinfection consisted of iodophor treatment at 100 ppm for 60 min. All eggs were incubated in TSB and monitored for bacterial growth. No growth was observed from disinfected eggs. However, from non‐disinfected eggs, C. maltaromaticum was isolated from the surface of 25% of individual unfertilised and 53% of fertilised eggs. V. salmoninarum was only isolated from non‐disinfected fertilised eggs. In year two, the process was repeated, though all eggs were fertilised and iodophor disinfected at 100 ppm for 30 min. Again, the pathogens were present on only a small number of disinfected eggs— V. salmoninarum and C. maltaromaticum were detected from the surface of one and five eggs respectively. Throughout the study we found no evidence of intra‐ova transmission from disinfected eggs. The study also demonstrates that iodophor is highly efficacious in reducing the prevalence and transmission risk of these pathogens.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

The cyanobacterial toxins BMAA and 2,4-DAB perturb the l-serine biosynthesis pathway and induce systemic changes in energy metabolism in human neuroblastoma cells: A proteomic study - Lisa Pu; Joel R. Steele; Connor R. Phillips; Jake P. Violi; Kenneth J. Rodgers (Toxicology in Vitro, 2025)

Space and ground-based measurements of negative cloud-to-ground strokes with and without significant continuing currents - Megan D. Mark; Amitabh Nag; Kenneth L. Cummins; Mathieu N. Plaisir; Dylan J. Goldberg; Phillip M. Bitzer; Abdullah Y. Imam; Hamid K. Rassoul (Atmospheric Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Development and testing of a mechanistic potential niche model of riparian tree seedling recruitment - Sierra J. Phillips; Gregory B. Pasternack; Kenneth Larrieu (Ecological Modelling, 2025)

A comprehensive review of the proline mimic azetidine-2-carboxylic acid (A2C) - Kenneth J. Rodgers; James Kabalan; Connor R. Phillips (Toxicology, 2025)

Leveraging Maker Learning in STEM to Promote Children’s Interest in Cancer Research: A Pilot Program - Kenneth P. Tercyak; Mary Rose Yockel; Jacqueline Eyl; Chiranjeev Dash; Dorothy Jones-Davis; Marcelo M. Sleiman; Liza Manfred; Dia Stone; Karen Howenstein; Denise Flessate Harley; Mingqian Liu; Catherine J. Scharon; et al. (Journal of Cancer Education, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Multi-proxy paleohydrological and paleoecological reconstruction of a subaquatic cave in western Cuba - Matthew C. Peros; Shawn Collins; Joao Gabriel Martínez-López; Lázaro W. Viñola López; Miguel Angel Pereira Sosa; Laurence Forget Brisson; François Hardy; Michel Lamothe; Peter J. van Hengstum; Bil Phillips; Kenneth Broad; Jill Heinerth; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Metabolic and molecular responses of human patellar tendon to concentric- and eccentric-type exercise in youth and older age - Hannah Crossland; Matthew S. Brook; Jonathan I. Quinlan; Martino V. Franchi; Bethan E. Phillips; Daniel J. Wilkinson; Constantinos N. Maganaris; Paul L. Greenhaff; Nathaniel J. Szewczyk; Kenneth Smith; Marco V. Narici; Philip J. Atherton (GeroScience, 2023)
Exercise training can induce adaptive changes to tendon tissue both structurally and mechanically; however, the underlying compositional changes that contribute to these alterations remain uncertain in humans, particularly in the context of the ageing tendon. The aims of the present study were to determine the molecular changes with ageing in patellar tendons in humans, as well as the responses to exercise and exercise type (eccentric (ECC) and concentric (CON)) in young and old patellar tendon. Healthy younger males (age 23.5 ± 6.1 years; n = 27) and older males (age 68.5 ± 1.9 years; n = 27) undertook 8 weeks of CON or ECC training (3 times per week; at 60% of 1 repetition maximum (1RM)) or no training. Subjects consumed D 2 O throughout the protocol and tendon biopsies were collected after 4 and 8 weeks for measurement of fractional synthetic rates (FSR) of tendon protein synthesis and gene expression. There were increases in tendon protein synthesis following 4 weeks of CON and ECC training ( P < 0.01; main effect by ANOVA), with no differences observed between young and old males, or training type. At the transcriptional level however, ECC in young adults generally induced greater responses of collagen and extracellular matrix-related genes than CON, while older individuals had reduced gene expression responses to training. Different training types did not appear to induce differential tendon responses in terms of protein synthesis, and while tendons from older adults exhibited different transcriptional responses to younger individuals, protein turnover changes with training were similar for both age groups.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The Combined Oral Stable Isotope Assessment of Muscle (COSIAM) reveals D-3 creatine derived muscle mass as a standout cross-sectional biomarker of muscle physiology vitality in older age - Jessica Cegielski; Matthew S. Brook; Bethan E. Phillips; Catherine Boereboom; Amanda Gates; John F. R. Gladman; Kenneth Smith; Daniel J. Wilkinson; Philip J. Atherton (GeroScience, 2022)
Validated diagnostics of skeletal muscle vitality could benefit clinical and basic science in terms of mechanistic insights and in determining the efficacy of interventions, e.g. exercise/pharmaceuticals/nutrients. We recently developed a Combined Oral Assessment of Muscle (COSIAM) that can be used to simultaneously quantify whole-body muscle mass (WBMM), muscle protein synthesis (MPS) and muscle protein breakdown (MPB). Here, we aimed to establish, in a cross-sectional fashion, links between COSIAM parameters and established aspects of muscle function. We recruited 37 healthy older adults (male (M):female (F) (21/16); 72 ± 5 y)) into a 3-day trial. Subjects consumed D 3 -creatine (D 3 -Cr dilution to assess WBMM), D 2 O (MPS by incorporation of alanine) and D 3 -3-methylhistidine (D 3 -MH dilution to assess MPB). A biopsy at day 3 was used to determine MPS, and blood/urine samples were collected to determine D 3 -Cr/D 3 -MH dilution for WBMM and MPB. Physiological measures of muscle mass (e.g. DXA/ultrasound) and function (e.g. handgrip strength, maximum voluntary contraction (MVC), one-repetition maximum (1-RM)) were ascertained. A stepwise linear regression approach was used to address links between facets of COSIAM (MPS, MPB, WBMM) and muscle physiology. Despite expected differences in muscle mass, there were no significant differences in MPS or MPB between sexes. WBMM as measured using D 3 -Cr positively correlated with DXA-derived lean body mass (LBM) and appendicular LBM (ABLM). Stepwise linear regression was used to assess which combination of MPS, MPB, D 3 -Cr and absolute synthesis rate (ASR) best predicted physiological measures of muscle health in these older adults. D 3 -Cr WBMM alone was the best predictor of handgrip, 1RM and MVC, and outperformed more traditional measures of muscle mass by DXA. The COSIAM approach substantiates D 3 -Cr as a robust biomarker of multiple muscle physiology health biomarkers. Future work using COSIAM should focus upon how and which parameters it can inform upon in relation to disease progression and the efficacy of interventions.

Diverse native island flora shows rapid initial passive recovery after exotic herbivore removal on Santa Rosa Island, California - Diane M. Thomson; A. Kathryn McEachern; Emily L. Schultz; Kenneth Niessen; Dieter Wilken; Katherine Chess; Lauren F. Cole; Ruth Y. Oliver; Jennifer D. Phillips; Acadia Tucker (Biological Invasions, 2022)

Development of duplex qPCR targeting Carnobacterium maltaromaticum and Vagococcus salmoninarum - Isaac Standish; Rebekah McCann; Corey Puzach; Eric Leis; Jennifer Bailey; Sara Dziki; Ryan Katona; Ellen Lark; Carey Edwards; Brandon Keesler; Stephen Reichley; Stacy King; et al. (Journal of Fish Diseases, 2022)
In November 2018, Vagococcus salmoninarum was identified as the causative agent of a chronic coldwater streptococcosis epizootic in broodstock brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery in Wisconsin, USA. By February 2019, the epizootic spread to adjacent raceways containing broodstock lake trout ( Salvelinus namaycush ), whereby fish were found to be coinfected with Carnobacterium maltaromaticum and V . salmoninarum . To differentiate these two pathogens and determine the primary cause of the lake trout morbidity, a quantitative real‐time PCR (qPCR) was developed targeting the C . maltaromaticum phenylalanyl‐tRNA synthase alpha subunit ( pheS ) gene. The qPCR was combined with a V . salmoninarum qPCR, creating a duplex qPCR assay that simultaneously quantitates C. maltaromaticum and V . salmoninarum concentrations in individual lake trout tissues, and screens presumptive isolates from hatchery inspections and wild fish from national fish hatchery source waters throughout the Great Lakes basin. Vagococcus salmoninarum and C. maltaromaticum were co‐detected in broodstock brook trout from two tribal hatcheries and C. maltaromaticum was present in wild fish in source waters of several national fish hatcheries. This study provides a powerful new tool to differentiate and diagnose two emerging Gram‐positive bacterial pathogens.

Strong and lasting impacts of past global warming on baleen whales and their prey - Andrea A. Cabrera; Elena Schall; Martine Bérubé; Pia Anderwald; Lutz Bachmann; Simon Berrow; Peter B. Best; Phillip J. Clapham; Haydée A. Cunha; Luciano Dalla Rosa; Carolina Dias; Kenneth P. Findlay; et al. (Global Change Biology, 2022)
Global warming is affecting the population dynamics and trophic interactions across a wide range of ecosystems and habitats. Translating these real‐time effects into their long‐term consequences remains a challenge. The rapid and extreme warming period that occurred after the Last Glacial Maximum (LGM) during the Pleistocene–Holocene transition (7–12 thousand years ago) provides an opportunity to gain insights into the long‐term responses of natural populations to periods with global warming. The effects of this post‐LGM warming period have been assessed in many terrestrial taxa, whereas insights into the impacts of rapid global warming on marine taxa remain limited, especially for megafauna. In order to understand how large‐scale climate fluctuations during the post‐LGM affected baleen whales and their prey, we conducted an extensive, large‐scale analysis of the long‐term effects of the post‐LGM warming on abundance and inter‐ocean connectivity in eight baleen whale and seven prey (fish and invertebrates) species across the Southern and the North Atlantic Ocean; two ocean basins that differ in key oceanographic features. The analysis was based upon 7032 mitochondrial DNA sequences as well as genome‐wide DNA sequence variation in 100 individuals. The estimated temporal changes in genetic diversity during the last 30,000 years indicated that most baleen whale populations underwent post‐LGM expansions in both ocean basins. The increase in baleen whale abundance during the Holocene was associated with simultaneous changes in their prey and climate. Highly correlated, synchronized and exponential increases in abundance in both baleen whales and their prey in the Southern Ocean were indicative of a dramatic increase in ocean productivity. In contrast, the demographic fluctuations observed in baleen whales and their prey in the North Atlantic Ocean were subtle, varying across taxa and time. Perhaps most important was the observation that the ocean‐wide expansions and decreases in abundance that were initiated by the post‐LGM global warming, continued for millennia after global temperatures stabilized, reflecting persistent, long‐lasting impacts of global warming on marine fauna.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Six weeks of high-intensity interval training enhances contractile activity induced vascular reactivity and skeletal muscle perfusion in older adults - Philip J. J. Herrod; Philip J. Atherton; Kenneth Smith; John P. Williams; Jonathan N. Lund; Bethan E. Phillips (GeroScience, 2021)
Impairments in muscle microvascular function are associated with the pathogenesis of sarcopenia and cardiovascular disease. High-intensity interval training (HIIT) is an intervention by which a myriad of beneficial skeletal muscle/cardiovascular adaptations have been reported across age, including capillarisation and improved endothelial function. Herein, we hypothesised that HIIT would enhance muscle microvascular blood flow and vascular reactivity to acute contractile activity in older adults, reflecting HIIT-induced vascular remodelling. In a randomised controlled-trial, twenty-five healthy older adults aged 65–85 years (mean BMI 27.0) were randomised to 6-week HIIT or a no-intervention control period of an equal duration. Measures of microvascular responses to a single bout of muscle contractions (i.e. knee extensions) were made in the m. vastus lateralis using contrast-enhanced ultrasound during a continuous intravenous infusion of Sonovue™ contrast agent, before and after the intervention period, with concomitant assessments of cardiorespiratory fitness and resting blood pressure. HIIT led to improvements in anaerobic threshold (13.2 ± 3.4 vs. 15.3 ± 3.8 ml/kg/min, P < 0.001), dynamic exercise capacity (145 ± 60 vs. 159 ± 59 W, P < 0.001) and resting (systolic) blood pressure (142 ± 15 vs. 133 ± 11 mmHg, P < 0.01). Notably, HIIT elicited significant increases in microvascular blood flow responses to acute contractile activity (1.8 ± 0.63 vs. 2.3 ± 0.8 (arbitrary contrast units (AU), P < 0.01)), with no change in any of these parameters observed in the control group. Six weeks HIIT improves skeletal muscle microvascular responsiveness to acute contractile activity in the form of active hyperaemia-induced by a single bout of resistance exercise. These findings likely reflect reports of enhanced large vessel distensibility, improved endothelial function, and muscle capillarisation following HIIT. Moreover, our findings illustrate that HIIT may be effective in mitigating deleterious alterations in muscle microvascular mediated aspects of sarcopenia.

Combined in vivo muscle mass, muscle protein synthesis and muscle protein breakdown measurement: a ‘Combined Oral Stable Isotope Assessment of Muscle (COSIAM)’ approach - Jessica Cegielski; Daniel J. Wilkinson; Matthew S. Brook; Catherine Boereboom; Bethan E. Phillips; John F. R. Gladman; Kenneth Smith; Philip J. Atherton (GeroScience, 2021)
Optimising approaches for measuring skeletal muscle mass and turnover that are widely applicable, minimally invasive and cost effective is crucial in furthering research into sarcopenia and cachexia. Traditional approaches for measurement of muscle protein turnover require infusion of expensive, sterile, isotopically labelled tracers which limits the applicability of these approaches in certain populations (e.g. clinical, frail elderly). To concurrently quantify skeletal muscle mass and muscle protein turnover i.e. muscle protein synthesis (MPS) and muscle protein breakdown (MPB), in elderly human volunteers using stable-isotope labelled tracers i.e. Methyl-[D 3 ]-creatine (D 3 -Cr), deuterium oxide (D 2 O), and Methyl-[D 3 ]-3-methylhistidine (D 3 -3MH), to measure muscle mass, MPS and MPB, respectively. We recruited 10 older males (71 ± 4 y, BMI: 25 ± 4 kg . m 2 , mean ± SD) into a 4-day study, with DXA and consumption of D 2 O and D 3 -Cr tracers on day 1. D 3 -3MH was consumed on day 3, 24 h prior to returning to the lab. From urine, saliva and blood samples, and a single muscle biopsy (vastus lateralis), we determined muscle mass, MPS and MPB. D 3 -Cr derived muscle mass was positively correlated to appendicular fat-free mass (AFFM) estimated by DXA (r = 0.69, P = 0.027). Rates of cumulative myofibrillar MPS over 3 days were 0.072%/h (95% CI, 0.064 to 0.081%/h). Whole-body MPB over 6 h was 0.052 (95% CI, 0.038 to 0.067). These rates were similar to previous literature. We demonstrate the potential for D 3 -Cr to be used alongside D 2 O and D 3 -3MH for concurrent measurement of muscle mass, MPS, and MPB using a minimally invasive design, applicable for clinical and frail populations.

Muscle and tendon adaptations to moderate load eccentric vs. concentric resistance exercise in young and older males - Jonathan Iain Quinlan; Martino Vladimiro Franchi; Nima Gharahdaghi; Francesca Badiali; Susan Francis; Andrew Hale; Bethan Eileen Phillips; Nathaniel Szewczyk; Paul Leonard Greenhaff; Kenneth Smith; Constantinos Maganaris; Phillip James Atherton; et al. (GeroScience, 2021)
Resistance exercise training (RET) is well-known to counteract negative age-related changes in both muscle and tendon tissue. Traditional RET consists of both concentric (CON) and eccentric (ECC) contractions; nevertheless, isolated ECC contractions are metabolically less demanding and, thus, may be more suitable for older populations. However, whether submaximal (60% 1RM) CON or ECC contractions differ in their effectiveness is relatively unknown. Further, whether the time course of muscle and tendon adaptations differs to the above is also unknown. Therefore, this study aimed to establish the time course of muscle and tendon adaptations to submaximal CON and ECC RET. Twenty healthy young (24.5 ± 5.1 years) and 17 older males (68.1 ± 2.4 years) were randomly allocated to either isolated CON or ECC RET which took place 3/week for 8 weeks. Tendon biomechanical properties, muscle architecture and maximal voluntary contraction were assessed every 2 weeks and quadriceps muscle volume every 4 weeks. Positive changes in tendon Young’s modulus were observed after 4 weeks in all groups after which adaptations in young males plateaued but continued to increase in older males, suggesting a dampened rate of adaptation with age. However, both CON and ECC resulted in similar overall changes in tendon Young’s modulus, in all groups. Muscle hypertrophy and strength increases were similar between CON and ECC in all groups. However, pennation angle increases were greater in CON, and fascicle length changes were greater in ECC. Notably, muscle and tendon adaptations appeared to occur in synergy, presumably to maintain the efficacy of the muscle–tendon unit.

Genome‐wide ancestry and introgression in a Zambian baboon hybrid zone - Kenneth L. Chiou; Christina M. Bergey; Andrew S. Burrell; Todd R. Disotell; Jeffrey Rogers; Clifford J. Jolly; Jane E. Phillips‐Conroy (Molecular Ecology, 2021)
Hybridization in nature offers unique insights into the process of natural selection in incipient species and their hybrids. In order to evaluate the patterns and targets of selection, we examine a recently discovered baboon hybrid zone in the Kafue River Valley of Zambia, where Kinda baboons ( Papio kindae ) and grey‐footed chacma baboons ( P. ursinus griseipes ) coexist with hybridization. We genotyped baboons at 14,962 variable genome‐wide autosomal markers using double‐digest RADseq. We compared ancestry patterns from this genome‐wide data set to previously reported ancestry from mitochondrial‐DNA and Y‐chromosome sources. We also fit a Bayesian genomic cline model to scan for genes with extreme patterns of introgression. We show that the Kinda baboon Y chromosome has penetrated the species boundary to a greater extent than either mitochondrial DNA or the autosomal chromosomes. We also find evidence for overall restricted introgression in the JAK/STAT signalling pathway. Echoing results in other species including humans, we find evidence for enhanced and/or directional introgression of immune‐related genes or pathways including the toll‐like receptor pathway, the blood coagulation pathway, and the LY96 gene. Finally we show enhanced introgression and excess chacma baboon ancestry in the sperm tail gene ODF2 . Together, our results elucidate the dynamics of introgressive hybridization in a primate system while identifying genes and pathways possibly under selection.

Preformulation Characterization of Griffithsin, a Biopharmaceutical Candidate for HIV Prevention - Lindsay F. Kramzer; Krystal T. Hamorsky; Phillip W. Graebing; Lin Wang; Joshua L. Fuqua; Nobuyuki Matoba; Amanda B. Lasnik; Bernard J. Moncla; Junmei Zhang; Kenneth E. Palmer; Lisa C. Rohan (AAPS PharmSciTech, 2021)

Characteristics of Transgender Patient Cases Managed by a Toxicologist: an Analysis of the Toxicology Investigator’s Consortium (ToxIC) Registry: January 2017–June 2019 - Ryan M. Surmaitis; Marna Rayl Greenberg; Natalie E. Ebeling-Koning; Phillip M. Grenz; Cody R. McWhirter; Beth A. Careyva; Judith N. Sabino; Matthew D. Cook; Robert D. Cannon; Andrew L. Koons; Kenneth D. Katz; Hope Kincaid; et al. (Journal of Medical Toxicology, 2021)

The legacy of biogeographic history on the composition and structure of Andean forests - Sebastián González‐Caro; Álvaro Duque; Kenneth J. Feeley; Edersson Cabrera; Juan Phillips; Sebastián Ramirez; Adriana Yepes (Ecology, 2020)
The biogeographic origin of species may help to explain differences in average tree height and aboveground biomass (AGB) of tropical mountain forests. After the Andean uplift, small‐statured trees should have been among the initial colonizers of the highlands (new cold environment) from the lowland tropics, since these species are pre‐adapted to cold conditions with narrow vessels that are relatively resistant to freezing. If the descendants of these small‐statured clades continue to dominate tropical highland forests, there will be a high co‐occurrence of close relatives at high elevations. In other words, this scenario predicts a systematic decline in tree size, AGB, and phylogenetic diversity with elevation. In contrast, the colonization of Andean forests by some large‐statured clades that originated in temperate regions may modify this expectation and promote a mixing of tropical and temperate clades, thereby increasing the phylogenetic diversity in tropical highland forests. This latter scenario predicts an increase or no change of tree size, AGB, and phylogenetic diversity with elevation. We assessed how the historical immigration of large‐statured temperate‐affiliated tree lineages adapted to cold conditions may have influenced the composition and structure of Andean forests. Specifically, we used 92 0.25‐ha forest inventory plots distributed in the tropical Andes Mountains of Colombia to assess the relationship between the phylogenetic diversity and AGB along elevational gradients. We classified tree species as being either “tropical affiliated” or “temperate affiliated” and estimated their independent contribution to forest AGB. We used structural equation modeling to separate the direct and indirect effect of elevation on AGB. We found a hump‐shaped relationship of phylogenetic diversity, AGB, and tree size with elevation. The high phylogenetic diversity found between 1,800–2,200 m above sea level (asl) was due to the mixing of highland floras containing many temperate‐affiliated species, and lowland floras containing mostly tropical‐affiliated species. The high AGB in highland forests, which contrasted with the expected decline of AGB with elevation, was likely due to the significant contribution of temperate‐affiliated species. Our findings highlight the lasting importance of biogeographic history on the composition and structure of Andean mountain forests.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Vagococcus salmoninarum I—A chronic coldwater streptococcosis in broodstock brook trout ( Salvelinus fontinalis ) in Wisconsin, USA - Isaac Standish; Sara Erickson; Eric Leis; Wes Baumgartner; Thomas Loch; Christopher Knupp; Rebekah McCann; Corey Puzach; Ryan Katona; Ellen Lark; Jennifer Bailey; Jorge Buening; et al. (Journal of Fish Diseases, 2020)
In 2018, Vagococcus salmoninarum was isolated from two lots of broodstock “coaster” brook trout ( Salvelinus fontinalis ) containing ~1,500 fish at the Iron River National Fish Hatchery, at which time it was identified as the causative agent of a chronic coldwater streptococcosis epizootic. Clinical signs included exophthalmia, lethargy, erratic swimming and loss of equilibrium. Female fish experienced disproportionately higher morbidity and mortality than male co‐inhabitants, and routinely retained eggs following spawning. The most consistent gross clinical sign was heart pallor and turbid pericardial effusion. An attempted treatment using florfenicol was ineffective at halting the epizootic, which spanned more than a year and resulted in >50% mortality before remaining fish were culled. As there is no previous documentation of V. salmoninarum at this hatchery or in this species, it is still unclear what circumstances led to this epizootic. The inability to treat this chronic disease led to the loss of valuable broodstock, hampering ongoing fishery conservation efforts in the Great Lakes Basin.

Vagococcus salmoninarum II—qPCR, tropism and egg‐associated transmission - Isaac Standish; Eric Leis; Sara Erickson; Rebekah McCann; Corey Puzach; Ryan Katona; Ellen Lark; Jennifer Bailey; Eric Kleman; Jorge Buening; Carey Edwards; Thomas Loch; et al. (Journal of Fish Diseases, 2020)
Vagococcus salmoninarum was identified as the causative agent of a chronic epizootic in broodstock “coaster” brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery. The epizootic spanned more than a year, was unresponsive to multiple florfenicol treatments, and resulted in >50% mortality of the affected fish. The decision was made to cull the remaining fish during spawning, which presented an opportunity to more thoroughly examine V. salmoninarum sampling methods, organ tropism and vertical transmission. A newly developed qPCR targeting the pheS gene was used in concert with bacterial culture to show that V. salmoninarum indeed disproportionately affects females and has a tropism for female reproductive tissues. The study demonstrates that some female reproductive tissues (e.g. ovarian fluid, unfertilized eggs) are also an effective option for non‐lethal detection. Despite the widespread presence of V. salmoninarum in ovarian fluid and on egg surfaces, we found no evidence of intra‐ova transmission.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Scaling issues of neutral theory reveal violations of ecological equivalence for dominant Amazonian tree species - Edwin Pos; Juan Ernesto Guevara; Jean‐François Molino; Daniel Sabatier; Olaf S. Bánki; Nigel C.A. Pitman; Hugo F. Mogollón; Roosevelt García‐Villacorta; David Neill; Oliver L. Phillips; Carlos Cerón; Marcos Ríos Paredes; et al. (Ecology Letters, 2019)
Neutral models are often used as null models, testing the relative importance of niche versus neutral processes in shaping diversity. Most versions, however, focus only on regional scale predictions and neglect local level contributions. Recently, a new formulation of spatial neutral theory was published showing an incompatibility between regional and local scale fits where especially the number of rare species was dramatically under‐predicted. Using a forward in time semi‐spatially explicit neutral model and a unique large‐scale Amazonian tree inventory data set, we show that neutral theory not only underestimates the number of rare species but also fails in predicting the excessive dominance of species on both regional and local levels. We show that although there are clear relationships between species composition, spatial and environmental distances, there is also a clear differentiation between species able to attain dominance with and without restriction to specific habitats. We conclude therefore that the apparent dominance of these species is real, and that their excessive abundance can be attributed to fitness differences in different ways, a clear violation of the ecological equivalence assumption of neutral theory.

A potato model intercomparison across varying climates and productivity levels - David H. Fleisher; Bruno Condori; Roberto Quiroz; Ashok Alva; Senthold Asseng; Carolina Barreda; Marco Bindi; Kenneth J. Boote; Roberto Ferrise; Angelinus C. Franke; Panamanna M. Govindakrishnan; Dieudonne Harahagazwe; et al. (Global Change Biology, 2017)
A potato crop multimodel assessment was conducted to quantify variation among models and evaluate responses to climate change. Nine modeling groups simulated agronomic and climatic responses at low‐input (Chinoli, Bolivia and Gisozi, Burundi)‐ and high‐input (Jyndevad, Denmark and Washington, United States) management sites. Two calibration stages were explored, partial (P1), where experimental dry matter data were not provided, and full (P2). The median model ensemble response outperformed any single model in terms of replicating observed yield across all locations. Uncertainty in simulated yield decreased from 38% to 20% between P1 and P2. Model uncertainty increased with interannual variability, and predictions for all agronomic variables were significantly different from one model to another ( P ET ), nitrogen uptake, and water use efficiency as compared to dry matter. A minimum of five partial, or three full, calibrated models was required for an ensemble approach to keep variability below that of common field variation. Model variation was not influenced by change in carbon dioxide (C), but increased as much as 41% and 23% for yield and ET , respectively, as temperature (T) or rainfall (W) moved away from historical levels. Increases in T accounted for the highest amount of uncertainty, suggesting that methods and parameters for T sensitivity represent a considerable unknown among models. Using median model ensemble values, yield increased on average 6% per 100‐ppm C, declined 4.6% per °C, and declined 2% for every 10% decrease in rainfall (for nonirrigated sites). Differences in predictions due to model representation of light utilization were significant ( P

Placental ABC Transporters: Biological Impact and Pharmaceutical Significance - Anand A. Joshi; Soniya S. Vaidya; Marie V. St-Pierre; Andrei M. Mikheev; Kelly E. Desino; Abner N. Nyandege; Kenneth L. Audus; Jashvant D. Unadkat; Phillip M. Gerk (Pharmaceutical Research, 2016)

Genetic diversity and divergence in the fountain darter (Etheostoma fonticola): implications for conservation of an endangered species - Jeffrey B. Olsen; Andrew P. Kinziger; John K. Wenburg; Cara J. Lewis; Catherine T. Phillips; Kenneth G. Ostrand (Conservation Genetics, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Ecological mitigation of hillslope instability: ten key issues facing researchers and practitioners - Alexia Stokes; Grant B. Douglas; Thierry Fourcaud; Filippo Giadrossich; Clayton Gillies; Thomas Hubble; John H. Kim; Kenneth W. Loades; Zhun Mao; Ian R. McIvor; Slobodan B. Mickovski; Stephen Mitchell; et al. (Plant and Soil, 2014)

Responses to alcohol and cigarette use during ecologically assessed drinking episodes - Thomas M. Piasecki; Phillip K. Wood; Saul Shiffman; Kenneth J. Sher; Andrew C. Heath (Psychopharmacology, 2012)

Medical Students Educate Teens About Skin Cancer: What Have We Learned? - Jeanette M. Kamell; William Rietkerk; Ken Lam; Jason M. Phillips; Jashin J. Wu; Jerry L. McCullough; Kenneth G. Linden; Kathryn Osann (Journal of Cancer Education, 2011)

Corrigendum: 2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

A major QTL for common bacterial blight resistance derives from the common bean great northern landrace cultivar Montana No.5 - Phillip N. Miklas; Dermot P. Coyne; Kenneth F. Grafton; Nedim Mutlu; Jim Reiser; Dale T. Lindgren; Shree P. Singh (Euphytica, 2003)

The symbiotic role of marine microbes on living surfaces - Evelyn Armstrong; Liming Yan; Kenneth G. Boyd; Phillip C. Wright; J. Grant Burgess (Hydrobiologia, 2001)